KARAKTER WIRAUSAHA DAN EFISIENSI PADA INDUSTRI MIKRO PANGAN OLAHAN DI D.I.Y - Triwara Buddhi Satyarini, Dwidjono Hadi Darwanto, Jangkung Handoyo, dan Slamet Hartono (Universitas 17 Agustus 1945 Samarinda, 2014)
Entrepreneurial Character study of the micro firm of food made in the province of Yogyakarta , includes 5 districts . The samples of firm’s owner are determined that its the most of business units in each district . The study aims to determine the character of the entrepreneurs and analyzed its relationship with business performance , especially in terms of the efficiency of their business . To find out the entrepreneurial character with descriptive analysis based on data assessed with Liekert’s scales and to determine the relationship between entrepreneurial character with efficiency in its business performance is analyzed with path analysis. The results of the analysis are that the character entrepreneurial businessmen in general less strong . Economic and environmental factors , including a conducive physical environment factors , although for less supportive social environment factors , only family support is high . Support institutional environmental factors and low management capacity . Character entrepreneurial achievement motivation and orientation of future significant effect on efficiency , the ability to build business networks and face changes significantly influence the development gains , the ability to face changes and external factors have a significant effect on productivity .